2020
DOI: 10.1002/cb.1891
|View full text |Cite
|
Sign up to set email alerts
|

Impact of TV dramas on consumers' travel, shopping and purchase intentions

Abstract: Countries are increasingly competing with each other to attract tourists. However, little is known about how consumers' tourism-related behaviors respond to country image endeavors, such as TV dramas. We propose that as an important image source TV dramas from a country contribute to crafting the country's brand image and thereby influence viewers' tourism related intentions. Considering the case of Turkish TV dramas and drawing on the Hierarchical Decision Model (HDM), a survey of 400 Arab viewers revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The logic of cultivation supports a similar notion that exposure to TV should have a more basic effect on behavior through shaping primary beliefs and attitudes. Ertz et al (2021) also found that exposure to Turkish TV drama relates indirectly to viewers' intentions to shop in Turkey. Furthermore, according to the NAM, activation of personal norms requires awareness of consequences (e.g., wasting food generates billion tons of CO 2 ), and ascribed responsibility (i.e., holding oneself responsible for the consequences of wasting food).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The logic of cultivation supports a similar notion that exposure to TV should have a more basic effect on behavior through shaping primary beliefs and attitudes. Ertz et al (2021) also found that exposure to Turkish TV drama relates indirectly to viewers' intentions to shop in Turkey. Furthermore, according to the NAM, activation of personal norms requires awareness of consequences (e.g., wasting food generates billion tons of CO 2 ), and ascribed responsibility (i.e., holding oneself responsible for the consequences of wasting food).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…For example, there is no analysis of the possibility that an overall positive projected image in a production might generate a negative perceived image. Only a few studies point to this possibility when they relate audiovisual productions to other media texts (Nanjangud & Reijnders, 2020;Ozretic-Dosen et al, 2018;Ertz et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is significant that all the articles that draw on textual theory and analysis attempt to go beyond a description of content or effects to take an explanatory approach, in an effort to establish how and why audiovisual fiction influences destination image a series on its image. A positive image projected by audiovisual fiction productions can compensate for negative images projected by news media, but the latter may also eclipse the effect of the former (Nanjangud & Reijnders, 2020;Ozretic-Dosen et al, 2018;Ertz et al, 2020).…”
Section: Negative Storylines Media Exposure and Visitsmentioning
confidence: 99%
“…Turkish TV dramas contribute to crafting the country's brand image and thereby influence viewers' travel-related intentions. A survey of 400 Arab viewers revealed that exposure to Turkish TV dramas results in increased intentions to visit and shop in Turkey as well as to purchase products made in Turkey (Ertz, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%